Contemporary Features and Challenges of Democratic Governance of the European Union (Journal of Advanced Research in Social Sciences, 2025)
This article describes the structure of the economic and political system of the European Union through the prism of democracy. It analyses the notion of democratic governance of the European Union, grounded on its key institutions - the European Commission, the European Council and the European Parliament. The author highlights the complexity of the EU as a supranational organisation where legislative, executive and judicial powers are intertwined. Consequences of the 2024 European Parliament elections and the growing influence of far-right parties, leading to increased political polarisation, are highlighted. While reviewing methods and theories, the paper examines reforms such as the direct election of the President of the European Commission, the strengthening of the Parliament and digitalisation that could strengthen the EU's democracy and effectiveness. The paper in its approach provides a robust foundation for further research and a deeper exploration of EU democracy.